Local Wisdom As Cultural Pedagogy: Membangun Identitas dan Ketahanan Sosial Peserta Didik - Sri Ilham Nasution; Khomsahrial Romli; Muhammad Mawardi J; Fauzi Nadziiran Haq (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Globalization and the penetration of digital culture have accelerated the homogenization of values, which has weakened the cultural identity and social character of the younger generation. This condition places local wisdom as a source of values that not only needs to be preserved but also systematically transformed in education. This article offers a critical analysis of the integration of local wisdom in character education as a mechanism for social transformation. Using a structured literature review approach, this study analyzes the concept of local wisdom, the role of teachers as agents of cultural preservation, the challenges of implementation in the context of modern education, and strategic models for integrating local values into the curriculum and school culture. The findings show that local values such as gotong royong (mutual cooperation), tepa selira (harmony), Tri Hita Karana (harmony between humans, nature, and the divine), Silih Asah Asih Asuh (mutual encouragement, love, and care), ABS-SBK (mutual respect, honesty, and integrity), and various traditional philosophies of the archipelago have proven effective in strengthening students' social character, enhancing social cohesion, and strengthening national identity. However, obstacles such as the dominance of global culture, low cultural literacy among teachers, and weak national curriculum support are significant hindrances. This article proposes a three-layer integrative model of contextual curriculum, culture-based pedagogy, and participatory school culture as a strategy for transforming social values that are adaptive to the challenges of the digital age. The conclusion emphasizes that character education based on local wisdom is not only an instrument for cultural preservation but also a strategic framework for building social resilience and national identity amid rapid global change.